Meningkatkan Kemampuan Berbicara Anak Dengan Penerapan Metode Bercerita di Depan Kelas di Tk Garuda 005 Sawah - Nia Febriani; Masrul Masrul; Joni Joni (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low speaking ability of group B children at Garuda 005 Sawah Kindergarten, North Kampar District, Kampar Regency. The formulation of the problem in this study is “Can the application of the storytelling method in front of the class improve the speaking ability of children in kindergarten 005 Sawah?”. The purpose of this classroom action research is to improve children's speaking ability with the application of storytelling in front of the class at 005 Sawah Kindergarten. This research was conducted in 2 cycles and in each cycle consisted of two meetings consisting of the following activities: planning, implementation, observation, reflection. The research time was carried out from May 20 to May 28. The population and sample in this study were group B which amounted to 18 children, 9 boys and 9 girls. The data analysis technique in this research is quantitative descriptive technique. Data collection was done using observation sheets, and documentation. The results showed that the development of children's speaking ability starting from cycle I with a percentage of 55.54%. When carried out in the second cycle it increased to 94.99%. Based on the results obtained in cycle I and cycle II, it can be concluded that the development of children's speaking ability in storytelling activities in front of the class can improve speaking ability in children aged 5-6 years at Garuda 005 Sawah Kindergarten.